COPING WITH THE CHALLENGES OF GRADUATE UNEMPLOYMENT THROUGH APPROPRIATE CAREER COUNSELLING - Egbe-Okpenge, Enechojo G.; Abekhale, Samon Oloruda (Sokoto Educational Review, 2017)
The challenge of graduate unemployment in Nigeria has become a cancerous disease that is seemingly defying treatment. One can sadly notice that educated, capable and active citizens of this country are roaming about the street seeking for job opportunities to no avail. The situation is such that enforced idleness has been created by lack of employment opportunities. This paper believes that the cause of unemployment which include the white-collar job syndrome; the poor attitude of some employers towards employment; the economic decline due to poor orientation to duty, lack of dignity in labour and work study programme as well as high population growth became issues for discussion because of the inadequate career counseling received by job seekers while in school. Consequently; most of the affected individuals are experiencing some social, economic and psychological traumas that require urgent attention. This paper therefore, attempts to propose some appropriate career counseling strategies that can be employed in arresting the situation. Some useful recommendations that will faster the reduction of unemployment in Nigeria have been suggested. While one admits that unemployment cannot be completely wiped out, it is believed that a drastic reduction to a manageable level can be realized if appropriate and pivfessional career counseling is considered.